Is Empathic Regulation a Moral Virtue? - Songhorian, Sarah (Itinerari, 2023)
The aim of this paper is to investigate the relationship between the concepts of “empathy” and “virtue”. To this aim, I will distinguish two possible forms their relationship may take: empathy can either be conceived (a) as a virtue per se; or (b) as an enabling condition for virtues to develop. Pre-theoretically, we are driven to consider (a) as correct, and yet a better understanding of the concept of “empathy” shows that that is not the case. To argue against (a), I will discuss the problematic features of broad definitions of empathy (that make (a) seem trivially true; § 2). Before proposing a narrower definition – that I take to be useful to connect it with virtue (§ 4) –, I will focus more specifically on some of the problems empathy has (§ 3). Finally, I will sketch how empathic regulation, and not empathy by itself can make (b) true.